1976
DOI: 10.1002/aic.690220418
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between velocity profiles and drag reduction in turbulent fiber suspension flow

Abstract: Equilibrium data for the sorption of oxygen, nitrogen, carbon monoxide, and methane in 5A molecular sieve are analyzed in terms of a simple theoretical model isotherm. The model provides an excellent correlation of the single-component isotherms over the entire concentration range, and it is shown that equilibrium data for sorption of binary mixtures of these gases are correcdy predicted by the model using the parameters (Henry constants and molecular volumes) derived from analysis of the singlecomponent isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…These trends are consistent with available literature for channel flow with polymer additives (e.g. De Angelis et al 2002) and are common also to other drag reducing flows (Virk 1975;Lee & Duffy 1976;Tsinober 1990;De Angelis et al 2003;Van Den Berg et al 2005). Figure 2 shows instantaneous snapshots of a wall-parallel plane in the buffer region (5 < y + < 30).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These trends are consistent with available literature for channel flow with polymer additives (e.g. De Angelis et al 2002) and are common also to other drag reducing flows (Virk 1975;Lee & Duffy 1976;Tsinober 1990;De Angelis et al 2003;Van Den Berg et al 2005). Figure 2 shows instantaneous snapshots of a wall-parallel plane in the buffer region (5 < y + < 30).…”
Section: Resultssupporting
confidence: 86%
“…Hence, we argue that the turbophoretic drift is lower in all turbulent flows when drag is reduced, e.g. fibre and bubble suspensions and magnetohydrodynamics (MHD) (see Lee & Duffy 1976;Tsinober 1990;Van Den Berg et al 2005, among others). A simple predictive model is derived in the limit of small-particle inertia to quantify the reduction of turbophoresis.…”
Section: Introductionmentioning
confidence: 98%
“…It is generally believed that drag reduction is due to the suppression of turbulent eddies by fibers or other particles. Several studies have suggested that drag reduction in fiber suspensions is especially due to dampening of radial velocity fluctuations in the turbulent core, in contrast to drag reduction in polymer solutions, in which drag reduction is due to dampening near the wall . This implies less turbulent dispersion and reduced lateral mixing, which appears to contradict the experimental results of improved mixing for the hardwood fibers.…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand, Lee and Duffy [122] discovered that the near-wall flow behavior was unaffected by the presence of fibers, and they proposed that the DR by fibers was due to the turbulence suppression in the turbulent core region.…”
Section: Fibermentioning
confidence: 97%